Index for Measuring the Quality of Complementary Feeding Practices in Rural India (Journal of Health, Population and Nutrition, 2010)
This community-based cross-sectional study was undertaken to develop a complementary feeding index (CFI) to assess the adequacy of complementary feeding (CF) practices and determine its association with growth of infants, aged 6-12 months, in rural Indian population. The study was conducted in six villages of Ghaziabad district, Uttar Pradesh, India. A structured interview schedule was used for eliciting information from 151 mothers of infants, aged 6-12 months, on CF practices. Data on CF practices were scored using the CFI developed. Measurements of weight and length were taken. Bivariate and multivariate analyses were done using the SPSS software (version 13). The results revealed that the CF practices were suboptimal in the sample. The mean±standard deviation (SD) CFI scores ranged from a low value of 7.09±3.21 in 6-8 months old infants to a comparatively-higher value of 9.69±2.94 in 9-12 months old infants. Using the CFI it could be identified that infants (n=151) had poor dietary diversity, with only 31% and 18% of the infants reportedly being fed the recommended number of food-groups during 6-8 and 9-12 months respectively. The food-frequency scores of the CFI showed that cereals and diluted animal milk were the major foodgroups fed to the infants in this setting. Analysis of nutritional status revealed that 24.5% of the infants were stunted (length-for-age [LAZ]